Regulatory T cells in cattle and their potential role in bovine paratuberculosis - Coussens, Paul M.; Sipkovsky, Sue; Murphy, Brooke; Roussey, Jon; Colvin, Christopher J. (Comparative immunology, microbiology and infectious diseases, 2012)
The intracellular bacterium Mycobacterium avium subspecies paratuberculosis (MAP) causes Johne's disease in wild and domestic ruminants. Johne's disease presents as a chronic enteritis with severe inflammation of intestinal tissues, characterized by widespread infiltration of macrophages, the target cell of MAP. Clinical signs of Johne's disease are typically accompanied by a loss of peripheral CD4+ T cell responses to MAP antigens and an increase in anti-MAP serum IgG levels. Recently, it was proposed that regulatory T cells might develop over the lengthy course of subclinical MAP infection. In the past five years, significant progress in defining bovine regulatory T cells has been made. These studies grew out of observations that IL-10 is produced by PBMCs in response to MAP antigen stimulation and that neutralization of this IL-10 could enhance IFN-γ production from MAP-antigen reactive effector T cells. Depletion studies revealed that MAP responsive cell populations producing IL-10 were largely CD4+ and CD25+, although monocytes have also been shown to produce IL-10 in response to MAP. In addition, evidence for a regulatory population of γδ T cells has also begun to accumulate. We summarize current thinking regarding regulatory T cells in MAP infection and provide data suggesting a potential link between regulatory T cells, bovine leukemia virus, and MAP.